Numerical Simulation of the Damage Behavior of a Concrete Beam with an Anisotropic Damage Model - Long, Y.C.; Yu, C.T. (Проблемы прочности, 2018)
An anisotropic damage model was proposed to describe the nonlinear behavior of concrete beams under monotonic and cyclic loading. The hysteresis effect of concrete is approximately modeled by employing nonlinear loading/linear reloading stress paths in the model, which was implemented into ABAQUS. Linear, bilinear, exponential and Reinhardt strain softening functions are introduced to investigate their influence on accuracy of calculations.